Global burden of disease study on COPD in the older adult: comprehensive analysis of environmental factors and interaction effects - Wang, Yuwei; Jin, Li; Dong, Yuhui; Yang, Erche; Niu, Xiaoqun; Mao, Jianchuan; Yuan, Chaoqun; You, Bo; Wang, Yong; Chai, Yanling (Frontiers in Public Health, 2025)
BackgroundChronic obstructive pulmonary disease (COPD) is a leading global health issue, ranking fourth in mortality in 2021 per GBD 2021, with older adults most at risk due to aging-related vulnerabilities. Environmental factors like air pollution and temperature extremes are key contributors, with evidence suggesting their interaction worsens COPD. As the older adult population is projected to reach 2.1 billion by 2050, understanding these impacts is vital for public health.MethodUsing GBD 2021 data, we analyzed COPD burden in older adults (1990–2021) due to air pollution and non-optimal temperature. Joinpoint regression and Bayesian models assessed trends in age-standardized mortality (ASMR) and disability-adjusted life year (ASDR) rates globally, regionally, and nationally. Spearman’s correlation evaluated socio-demographic index (SDI) associations, and standardized exposure value (SEV) data examined air pollution-temperature interactions.ResultGlobally, most environmental COPD burdens declined or stabilized, but high temperature burdens rose (AAPC > 0, p < 0.05). By 2015, ambient PM2.5 overtook household air pollution as the top risk, with 2021 ASMR at 76.29 [54.62, 95.48] and ASDR at 1364.67 [981.69, 1687.82] per 100,000. Low- and middle-SDI regions, especially South and East Asia, faced the highest burdens, with rising PM2.5 and ozone impacts. Air pollution and temperature showed synergistic effects, with high temperature strongly correlating with increased PM2.5 and ozone exposure levels, amplifying COPD burden, except for household air pollution.ConclusionThis study reveals shifting COPD burdens, with ambient PM2.5 and high temperatures emerging as key challenges, particularly in lower-SDI areas. Synergistic air pollution-temperature effects highlight the need for integrated policies. These findings support targeted interventions to reduce COPD burden and enhance health equity in aging populations.